2011
DOI: 10.1038/ismej.2011.157
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and regulation of bacterioplankton respiratory quotient across freshwater environmental gradients

Abstract: Bacterioplankton respiration (BR) may represent the largest single sink of organic carbon in the biosphere and constitutes an important driver of atmospheric carbon dioxide (CO 2 ) emissions from freshwaters. Complete understanding of BR is precluded by the fact that most studies need to assume a respiratory quotient (RQ; mole of CO 2 produced per mole of O 2 consumed) to calculate rates of BR. Many studies have, without clear support, assumed a fixed RQ around 1. Here we present 72 direct measurements of bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
158
2
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 171 publications
(172 citation statements)
references
References 51 publications
10
158
2
2
Order By: Relevance
“…respired to O 2 consumed (e.g., oxalic acid, a known photochemical product, has an RQ of 4). Berggren et al (2012) found that for a large freshwater data set, RQ was between 0.5 and 2, with a large standard deviation. A strong variation in RQ in irradiated DOM relative to controls, or a change of RQ during the subsequent dark incubation will certainly influence all studies, ours included, that define an RQ a priori for calculating BLP concentrations.…”
Section: Discussionmentioning
confidence: 97%
“…respired to O 2 consumed (e.g., oxalic acid, a known photochemical product, has an RQ of 4). Berggren et al (2012) found that for a large freshwater data set, RQ was between 0.5 and 2, with a large standard deviation. A strong variation in RQ in irradiated DOM relative to controls, or a change of RQ during the subsequent dark incubation will certainly influence all studies, ours included, that define an RQ a priori for calculating BLP concentrations.…”
Section: Discussionmentioning
confidence: 97%
“…While there is a range of efficiencies with which the microbial community can access DOM (i.e. respiratory quotient RQ; Berggren et al, 2012), for the most part these boreal freshwater RQs fall within a relatively small range (0.5-2) and as such BOD can be used as an effective proxy for the biological reactivity or lability of the DOM (Miller et al, 2002;Asmala et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Boreal biomes contain the highest density of freshwater on Earth, yet this evidence for biologically degradable DOC is scattered and based on isolated components of the continental aquatic network. As a result, the overall susceptibility of DOC to photochemical and biological degradation, and how this susceptibility varies over gradients of increasing terrestrial influence and at scales relevant for continental C budgets, has not been well established 19,[33][34][35][36] .…”
mentioning
confidence: 99%